Barriers to Energy Efficiency Measures in Recycled Paper and Pulp Industry in India: An Interpretive Structural Modelling- Based Framework - Anand Narhari Sonsale, Yashpal, S. D. Pohekar, Jayant Purohit (International Journal of Modern Agriculture, 2021)
Paper and pulp industry is one of the top six energy intensive industriesin India. Even then available energy efficiency measuresface certain barriers to their implementation in paper and pulp industry. This study examines barriers to energy efficiency in the context ofrecycled fibre-based Paper and Pulp industry in India. The objective of this study is to pinpoint the barriers that are significantly important using interpretive structural modelling and develop a hierarchy to investigate the contextual relationship among these barriers. Results of this study show that Poor Information Quality regarding Energy Conservation Measures and Technical Risks emerge as the most important barriers that would drive all other barriers. The study has also performed â€œcross impact matrix multiplication applied to a classificationâ€ (MICMAC) analysis of the barriers to classify them based on the dispersal of their driving power and dependence power. It brings out Poor Information Quality regarding Energy Conservation Measures, Uncertainty about future energy prices and fiscal policies, Uncertainties regarding hidden costs and Technical risks as independent barriers having strong driving power but weak dependence power. Addressing these barriers would be the key to success for implementation of energy efficiency measures by any organization.